Proton exchange membrane‐based electrocatalytic systems for hydrogen production - Yangyang Zhou; Hongjing Zhong; Shanhu Chen; Guobin Wen; Liang Shen; Yanyong Wang; Ru Chen; Li Tao; Shuangyin Wang (Carbon Energy)
Abstract Hydrogen energy from electrocatalysis driven by sustainable energy has emerged as a solution against the background of carbon neutrality. Proton exchange membrane (PEM)‐based electrocatalytic systems represent a promising technology for hydrogen production, which is equipped to combine efficiently with intermittent electricity from renewable energy sources. In this review, PEM‐based electrocatalytic systems for H2 production are summarized systematically from low to high operating temperature systems. When the operating temperature is below 130°C, the representative device is a PEM water electrolyzer; its core components and respective functions, research status, and design strategies of key materials especially in electrocatalysts are presented and discussed. However, strong acidity, highly oxidative operating conditions, and the sluggish kinetics of the anode reaction of PEM water electrolyzers have limited their further development and shifted our attention to higher operating temperature PEM systems. Increasing the temperature of PEM‐based electrocatalytic systems can cause an increase in current density, accelerate reaction kinetics and gas transport and reduce the ohmic value, activation losses, ΔGH*, and power consumption. Moreover, further increasing the operating temperature (120–300°C) of PEM‐based devices endows various hydrogen carriers (e.g., methanol, ethanol, and ammonia) with electrolysis, offering a new opportunity to produce hydrogen using PEM‐based electrocatalytic systems. Finally, several future directions and prospects for developing PEM‐based electrocatalytic systems for H2 production are proposed through devoting more efforts to the key components of devices and reduction of costs.